2022
DOI: 10.2147/copd.s337354
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Particle-Induced Lung Injury and Iron Homeostasis

Abstract: It is proposed that the mechanistic basis for non-neoplastic lung injury with cigarette smoking is a disruption of iron homeostasis in cells after exposure to cigarette smoke particle (CSP). Following the complexation and sequestration of intracellular iron by CSP, the host response (eg, inflammation, mucus production, and fibrosis) attempts to reverse a functional metal deficiency. Clinical manifestations of this response can present as respiratory bronchiolitis, desquamative interstitial pneumonitis, pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 400 publications
(454 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, in smoking patients Fe complexation by CS leads to a more pronounced Fe mobilisation [ 12 , 34 36 , 39 ] and thus a continuous supply of Fe to the AFBs. Accordingly, smoking patients experience the formation of larger denser layers around their asbestos fibres and throughout their AFBs, resulting in smaller AFB diameters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in smoking patients Fe complexation by CS leads to a more pronounced Fe mobilisation [ 12 , 34 36 , 39 ] and thus a continuous supply of Fe to the AFBs. Accordingly, smoking patients experience the formation of larger denser layers around their asbestos fibres and throughout their AFBs, resulting in smaller AFB diameters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Smoking causes an inflammatory response in the lungs and represents a risk factor for pulmonary diseases like COPD. It also elevates soluble inflammatory markers in the bloodstream (34). It has been demonstrated that various types of inflammatory conditions and organ failure are associated with a drastic increase in PSP/reg protein levels, thus the inflammation in smokers' air spaces may increase their blood levels of PSP/reg (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of smoking is more dreaded in the homeostasis of microelements in particular, one of the most significant examples being the influence of smoking on iron homeostasis. Iron homeostasis of the cells gets disrupted when exposed to cigarette smoke particles, which ultimately is assumed to lead to the development of non-neoplastic injury of the lungs [ 30 ]. Even e-cigarettes interfere with the respiratory health of adolescents with asthma [ 31 ], and thus are no better alternative.…”
Section: Reviewmentioning
confidence: 99%